An efficient method of tortuosity estimation - Sobieski, W. (Archives of Mechanics, 2022)
The paper presents a comparative analysis of tortuosity calculations in two types of 2D random geometries: with non-overlapping circles and with overlapping squares. Both geometries were converted to binary geometries with different resolution. Next, simulations involving the Lattice Boltzmann Method were performed to obtain velocity fields in a pore space. Based on the obtained velocity fields, Hydraulic tortuosity and streamline tortuosity were calculated, based on the obtained velocity fields, for all considered cases. Hydraulic tortuosity was calculated with the methodology proposed by Koponen et al., whereas streamline tortuosity was determined with the use of a new iterative algorithm. Two variants of the algorithm were proposed. Additionally, the obtained results were compared with selected formulas from the literature. The study demonstrated that calculations of streamlines exiting local inlet velocity maxima are a good alternative to calculations where all possible streamlines are taken into account. Computation time was significantly shorter and estimation quality was comparable.